Sob a perspectiva do letramento literário: a casa do leitor - Corsso, Josaine Aparecida (2018)
This project presents an interventional proposal of literary reading and creative writing for seventh graders of a public school. The research starts from the need to recover the importance of Literature in the school context, as traditional methods often do not reach the objective of forming readers. With this, we seek a method of teaching that allows enlarging the literary view of the student reader on the home environment, an environment that stars in the literary works selected for this research. Thus, through a theoretical-methodological approach based on the basic sequence of literary literacy suggested by Rildo Cosson (2014), we elaborated reading and writing workshops for the theme presented in the works A casa da madrinha, by Lygia Bojunga and Por parte de pai, by Bartolomeu Campos de Queirós. The purpose is that by reading these literary texts with imagery and fictional descriptions of houses and the relationships that exist between this space and the characters, the student readers, in dialogue with literature, can reflect on their identity and create their own literary description of the place in which they live. The work proposal consists of carrying out a bibliographical study on the schooling of literature, literary literacy and the house as literary space. From the contributions of the theoretical apparatuses, we propose the comparison of two textual productions of the students about the space in which they live, being one before and another subsequent to the activities of creative writing developed in the workshops. Through a descriptive and interpretative analysis of the textual productions mentioned, we intend to evaluate if the suggested action research can contribute to the process of literary literacy of the student reader. Thus, we hope, with this work, to provide effective practices of literary reading and creative writing.